THE NEXUS OF SELF-ASSESSMENT, MONEY ETHICS, AND TAX SANCTIONS IN TAX COMPLIANCE - Darmawati; Joham, Cornelia Marcheline; Nurleni (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2024)
This research seeks to explore and examine the connection between self-assessment systems, money ethics, and tax sanctions on individuals' views regarding tax evasion. Primary data were gathered using questionnaires distributed at the North Makassar KPP Pratama research location, involving a sample of 100 taxpayers. Quantitative methods were employed to test the analytical model using multiple linear regression. The findings indicate that the self-assessment system negatively impacts tax evasion, while money ethics have a positive impact. Conversely, tax sanctions do not have a significant effect on tax evasion. Overall, self-assessment systems, money ethics, and tax sanctions collectively influence taxpayers' views on tax evasion. This research is crucial for further examination as it can provide valuable insights for the government in formulating tax regulations.